Primary student teachers' professional identity tensions: The construction and psychometric quality of the professional identity tensions scale. (June 2019) - Hanna, Fadie; Oostdam, Ron; Severiens, Sabine E.; Zijlstra, Bonne J.H.
Highlights: A purely quantitative instrument for measuring professional identity tensions. Thirty-four items cover nine underlying professional identity tensions. Regular professional identity tensions and urban related tensions are considered. Acknowledge methods for scale development were followed. Abstract: This research aims to develop and validate an instrument for measuring primary student teachers' professional identity tensions. Based on dissonance theory, we transformed existing vignettes (Pillen, Den Brok, & Beijaard, 2013 ) into to a quantitative Professional Identity Tensions Scale (PITS) and added tensions regarding teaching in urban contexts. We examined the psychometric quality of the PITS by administering this scale to primary student teachers from teacher education institutions in urban areas across the Netherlands. Two studies were conducted in the process of validating the PITS. First, items were tested among a sample of 211 students to explore whether they measure underlying constructs of professional identity tensions. Second, retained items were administered to a new sample of 271 students. Confirmatory factor analysis demonstrated a similar factor structure. The final instrument includes 34 items rated on a 5-point Likert scale measuring nine different professional identity tensions. Implications for future research and practice are discussed.